Migrant Youths' Educational Achievement: The Role of Institutions - Deborah Cobb-Clark; Mathias Sinning; Steven Stillman (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2011)
We use 2009 Programme of International Student Assessment (PISA) data to link institutional arrangements in OECD countries to the disparity in reading, math, and science test scores for migrant and native-born students. We find that achievement gaps are larger for those migrant youths who arrive later and for those who do not speak the test language at home. Institutional arrangements often serve to mitigate the achievement gaps of some migrant students while leaving unaffected or exacerbating those of others. For example, earlier school starting ages help migrant youths in some cases, but by no means in all. Limited tracking on ability appears beneficial for migrants' relative achievement, while complete tracking and a large private school sector appear detrimental. Migrant students' achievement relative to their native-born peers suffers as educational spending and teachers' salaries increase, but is improved when examination is a component of the process for evaluating teachers.
Keywords: 330; Migrant Youths; PISA Test Scores; Schools; Institutions; Academic Achievement